Peningkatan Pengetahuan mengenai PHBS sebagai Program Promosi Kesehatan pada Tatanan Sekolah di SMPN 4 Sungguminasa Kabupaten Gowa - Andi Asrina; Yusriani, Yusriani (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
PHBS in schools is a set of efforts implemented by school members on the basis of awareness to prevent disease, create a clean and healthy environment, and improve health. The 2015 Indonesia Health Profile presents data that there are 68% of those who have a clean and healthy lifestyle in the school environment. Based on the results of observations at SMPN 4 Sungguminasa, problems related to the school were found with scattered trash, the condition of the toilets that were not clean, the sinks for washing hands were unhygienic and some were not proper, drainage conditions for handwashing did not flow so that water for washing hands accommodated, and many of the posters about health impact messages have been damaged. The purpose of community service is to increase the knowledge of SMPN 4 Sungguminasa students about PHBS. The method used in carrying out health promotion activities is conducting education by using the method of sticking posters in places that are easily seen and followed by conducting counseling and ending with a discussion/question and answer between the instructor and the audience (participants). The target participants for the service were representatives of grade 7 and 8 students, Osis administrators, and PMR administrators totaling 50 people. According to the results of the data from this activity the average result of the level of knowledge of students (i) in the very good category after being given education related to PHBS at SMPN 4 Sungguminasa was obtained 98.4% and the average result of the level of student knowledge (i) in the very good category after being given education related to drugs, it obtained 100%. In conclusion, community service activities through health promotion counseling methods and posters can very well increase the knowledge of SMPN 4 Sungguminasa students by 98.4%, so that all students, teachers and school educators are required to routinely implement PHBS at school.